POST-RELIGION: TRADITIONALISTS’ ANALYSIS - Kirill M. Tovbin (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Aim of the study is to describe the phenomenon of post-religion as a specific spiritual sphere of the Post-modernity. Methodology. In the introduction analyzed a variety of methodological approaches, opening his inadequacy applied to the spiritual sphere of Post-modernity: «classic» religious studies, religious studies of traditional spiritual movements and the post-modern religious studies, partly produced Traditionalist school, could - according to the author's hypothesis - become a methodological basis for the most complete analysis of post-religion. Scientific novelty. In the main part of the article crystallized the authorized concept of post-religion, its relation with traditional and religious spiritual realms. Post-religion is positioned as the top of secularism enshrined in the departure from the straight and aggressive secularism of the Modernity, but without recourse to Tradition. Post-religion a simulation spirituality, skillfully imitating the outer areas of traditional spirituality and creates a planar religiosity, radically preventing attached to the vertical line of Traditions. In this regard, are the main artificially selected parameters of post-religion: deconstruction, splitting, virtualization, and collage. Deconstruction is a transformation of spirituality in semiotic set for egocentric selectivity of modern believer. Post-religion’s splitting is deprivation of spirituality center, destruction of sacral Center and the transformation of spirituality in the plane on which the intellectual and sensual wandering post-believer from one semiotic island to another. Virtualization is a displacement field of spiritual tension in a completely virtual area, isolated from the natural conditions of existence and created as his replacement, network discussion sites and galleries. Collage is an arbitrary combination of different semiotic pieces of Tradition with the aim of creating a believable picture of tradition; it is collage leads to archaic forms of modern spirituality. Findings. Thus, based on the above study phenomenological illustrations, can declare one can argue that Post-modernity is much wider than the decadent direction of the culture is a radical shift of spirituality, the top of desacralization.